Sistem Forecasting Perencanaan Produksi dengan Metode Single Exponential Smoothing Pada Home Industry Tempe Putera Sejahtera - Audinasyah, Chika Syifa; Solehudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Home Industry Tempe Putera Sejahtera is an attempt to produce tempeh which is located in Lemah Abang, Karawang. The purpose of this study is to know and predict the amount of tempe production in the next period. The method used for this research is Single Exponential Smoothing and the method used to measure the accuracy of the forecasting is the Mean Absolute Deviation (MAD), the Mean Square Error (MSE) and the Mean Average Percentage Error (Mape). The result of this study was the smallest number of values ​​in MAD by 73.75, the smallest number of values ​​in MSE was 5,738 and the smallest number of values ​​in the MAPE was 2.92%. The results show the effectiveness of the Single Exponential Smoothing method in providing accurate predictions for tempe production, helping businesses in optimizing production planning and minimizing waste.